When a solitary plasmacytoma is just the beginning… - Rasche, Leo; Weinhold, Niels (Blood, 2023)
In this issue of Blood, Yadav et al provide the first evidence for the prognostic role of myeloma high-risk chromosomal abnormalities in solitary bone plasmacytoma (SBP).1Currently, SBP is considered a low-risk disease condition, and radiation therapy is curative for roughly one-half of the patients. However, Yadav et al convincingly show that this paradigm does not hold true anymore. Despite radiation therapy, patients presenting with at least 1 of the high-risk markers +1q and del(17p) have a median time to progression to symptomatic myeloma of only 8 months, demonstrating that there is a group of patients who need systemic treatment right away to prevent further end organ damage. Thus, high-risk cytogenetics is a potential biomarker for clinical decision making in SBP. It is fascinating that once again the molecular makeup of clonal plasma cells dictates the course of the disease. This is in line with the recent finding that patients with poor-prognosis myeloma can present with high-risk disease markers in focal lesions only, highlighting that high-risk disease drives prognosis, even if distributed heterogeneously in the bone marrow.2